PERLINDUNGAN HUKUM TERHADAP KONSUMEN APARTEMEN TERKAIT HAK ATAS TANAH BERSAMA - Mayasari, Diah Kartika; Riyanto, Slamet; Fadillah, Syarif (Jurnal Hukum Jurisdictie, 2019)
Diah Kartika Mayasari, 1220140030. Flats are built as an effort to meet the need for housing, especially in the city and supporting areas around it which are increasingly difficult to meet due to the high rate of population increase while the land area does not increase. With increasingly affordable prices, strategic location and complete facilities of the apartment becomes its own attraction for the community. But in practice in the field, many consumers who buy apartments without knowing the status of ownership of the land where the apartment stands. If the status of the land is SHM atan HGB Murni then there is no problem, The problem that may arise is if the status of the land is HGM above the Management Thing (HPL), if HGB has matured and the government or third party as the landowner does not want to extend the HGB, then it is entitled to take back the land. The purpose of this study is to find out how to regulate land rights related to land with apartments, how the practice of providing information by developers to prospective consumers regarding land rights with apartments and how legal protection of apartment consumers in disputes over shared land rights. The research method used is an empirical juridical method. The data collected is information relevant to the topic or problem that will or is being researched. Information can be obtained from books, research reports, scientific essays, theses, regulations, provisions and written sources both printed and electronic. In addition, data is also obtained from interviews with several developers and consumers of the apartment. The results showed that the majority of developers did not inform prospective consumers about the status of the land to be built unless asked by consumers. This led to allegations that developers could be hiding something that could one day harm consumers. The legal protection of consumer flats has been regulated in the Flats Act, so it does not use the Consumer Protection Act. Some provisions in it impose obligations to sellers (legal entities) to meet technical, administrative and civil requirements with the threat of administrative, civil or criminal sanctions.